Construction and Real Estate Dynamics - (:unkn) unknown (Londres: Palgrave Macmillan, 2003)
This collection deals with some interesting economic questions related to construction and real estate, namely how construction firms cope with the volatility of construction; whether speculative bubbles or market fundamentals drive those fluctuations; new techniques to predict construction demand; why the office market led the recent real estate cycle; and whether regulation is responsible for speculative behaviour.
Keywords: Construction; Real-Estate